Budding Yeast Chromosome Structure and Dynamics during Mitosis - Pearson, Chad G. (The Rockefeller University Press, 2001)
Using green fluorescent protein probes and rapid acquisition of high-resolution fluorescence images, sister centromeres in budding yeast are found to be separated and oscillate between spindle poles before anaphase B spindle elongation. The rates of movement during these oscillations are similar to those of microtubule plus end dynamics. The degree of preanaphase separation varies widely, with infrequent centromere reassociations observed before anaphase. Centromeres are in a metaphase-like conformation, whereas chromosome arms are neither aligned nor separated before anaphase. Upon spindle elongation, centromere to pole movement (anaphase A) was synchronous for all centromeres and occurred coincident with or immediately after spindle pole separation (anaphase B). Chromatin proximal to the centromere is stretched poleward before and during anaphase onset. The stretched chromatin was observed to segregate to the spindle pole bodies at rates greater than centromere to pole movement, indicative of rapid elastic recoil between the chromosome arm and the centromere. These results indicate that the elastic properties of DNA play an as of yet undiscovered role in the poleward movement of chromosome arms.